ASSESSMENT OF POTATO RESISTANCE TO SYNCHYTRIUM ENDOBIOTICUM - Przetakiewicz, Jarosław; Plich, Jarosław (Plant Breeding and Seed Science, 2017)
In Poland the Plant Breeding and Acclimatization Institute - National Research Institute (IHAR-PIB) is responsible for officially assessing the resistance of potato breeding lines and cultivars to Synchytrium endobi-oticum. In the official assessment of wart resistance the modified Glynne-Lemmerzahl method is used. A full cycle of assessment of the wart disease resistance requires 42 - 45 tubers per cultivar/breeding line. Forty two tubers are used in laboratory tests. To complete the laboratory tests, another 10 tubers are inoculated with winter sporangia of the fungus, using ring test. The final results are available after 3 years of investigation. If necessary, the full cycle of resistance tests to S. endobioticum can be performed during one year on 15 tubers in each of the 3 replications (45 tubers in total). Molecular verification of potato genotypes resistance to pathotype 1(D1) is possible with the use of SCAR marker Nl25-1400. Nevertheless, an official phenotypical assessment of advanced breeding lines, as the final verification of their resistance, is required.